2019
DOI: 10.3390/ijms20174227
|View full text |Cite
|
Sign up to set email alerts
|

The Reason for Growth Inhibition of Ulmus pumila ‘Jinye’: Lower Resistance and Abnormal Development of Chloroplasts Slow Down the Accumulation of Energy

Abstract: Ulmus pumila ‘Jinye’, the colorful leaf mutant of Ulmus pumila L., is widely used in landscaping. In common with most leaf color mutants, U. pumila ‘Jinye’ exhibits growth inhibition. In this study, U. pumila L. and U. pumila ‘Jinye’ were used to elucidate the reasons for growth inhibition at the physiological, cellular microstructural, and transcriptional levels. The results showed that the pigment (chlorophyll a, chlorophyll b, and carotenoids) content of U. pumila L. was higher than that of U. pumila ‘Jinye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Trans-cinnamate 4-monooxygenase that is also called as cinnamate 4-hydroxylase (C4H) participates in the synthesis of numerous polyphenoid compounds by plants when challenged by pathogens, such as flavones, isoflavonoids, and lignin (Zhu et al, 2020). The accumulation of the enzyme in our study could be related to the accumulation of flavones and isoflavonoids, increasing lignification of the cell wall and then enhance soybean resistance, which is similar to the results in Ulmus pumila (Zuo et al, 2019). Moreover, increased expression levels of seven CHS were identified in present study.…”
Section: Discussionsupporting
confidence: 86%
“…Trans-cinnamate 4-monooxygenase that is also called as cinnamate 4-hydroxylase (C4H) participates in the synthesis of numerous polyphenoid compounds by plants when challenged by pathogens, such as flavones, isoflavonoids, and lignin (Zhu et al, 2020). The accumulation of the enzyme in our study could be related to the accumulation of flavones and isoflavonoids, increasing lignification of the cell wall and then enhance soybean resistance, which is similar to the results in Ulmus pumila (Zuo et al, 2019). Moreover, increased expression levels of seven CHS were identified in present study.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, in the present study, a dark green leaf (GL) mutant with more developed and more closely arranged palisade tissue than normal leaf-color plants was reported. In general, thylakoids are carriers of pigments in plant leaves, and the accumulation of pigments is directly influenced by the stacking state of thylakoid layers [16]. Consistently, we also found that the lamellae were clear and that the stroma and grana were orderly, with more stacking and larger starch grains, as determined by observing the ultrastructure of the chloroplasts in GL leaves.…”
Section: Characterization Of Photosynthesis Between Wt and Gl Plantssupporting
confidence: 84%
“…Therefore, the reduction in Chl content and the occurrence of aberrant structural alterations in chloroplasts should be the primary factors contributing to our study's observed decrease in photosynthetic capacity. Comparable findings were observed in the yellow mutant of U. pumila [38]. As a consequence of compromised photosynthesis, mutant leaves also exhibit deficiencies in carbon skeletons and major carbon metabolism end-products, including flavonoids, leading to delayed plant growth [59].…”
Section: Discussionmentioning
confidence: 92%
“…Due to impaired photosynthesis, the yellow NAU31 mutant had impaired chloroplast structure and reduced Chl and Car content [35]. Although, in recent years, ornamental plants have also witnessed the emergence of Chl-deficiency mutants, including species like G. biloba [36], Quercus shumardii [37], Ulmus pumila [38], Lagerstroemia indica [39], and Acer palmatum [40]. However, there is a paucity of comprehensive investigations into the molecular mechanisms underlying ornamental leaf color mutants.…”
Section: Introductionmentioning
confidence: 99%